Omega-3 Polyunsaturate Fatty Acid Supplementation Potential to Improve Activity Components of Rheumatoid Arthritis: A Systematic Review - Hidayat, Nadia; Awalia, Awalia; Tambunan, Betty Agustina; Novida, Hermina (Universitas Airlangga, 2023)
Introduction: Rheumatoid arthritis (RA) is a chronic disease that causes deformity in most productive age and can lead to death as disease activity increases. Omega-3 polyunsaturated fatty acids have the potential to complement available therapies in reducing disease activity. Currently, the effect of omega-3 PUFAs on disease activity components is still unclear. The current systematic reviews determine the effect of omega-3 PUFAs' supplementation on the components of RA disease activity. Methods: This research is guided by the PRISMA guidelines systematically. Literature was searched in the databases: PubMed, MDPI, and Clinicaltrials.gov. The inclusion criteria used were: giving omega-3 PUFAs, free full-text, RCT, in English or Indonesian, assessing disease activity and its components; while the exclusion criteria were: unpublished, comparisons were inappropriate. Assessment of literature quality with the Cochrane Collaboration's tool. The study included six studies from 1994 to 2017. Results: The effect of omega-3 PUFAs is diversity in changes of disease activity in 4 of 5 studies. There are significant reductions in the number of joint pains in the literature by daily doses above 2.9 grams or at lower doses taking longer; and swollen joints in 2 studies that were only affected in doses above 2.9 grams. There are significant reductions in pain severity in the studies. Change increases with higher doses. There are variable LED and CRP changes. Conclusion: Depending on their dose and administration duration, omega-3 PUFAs can directly and indirectly affect disease activity through the influence of most of its components, namely: the number of joints affected and the degree of pain.